2018
DOI: 10.14221/ajte.2018v43n5.2
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Teacher Education and the Incoming Tide of Information Technology: A Contemporary Guitar Perspective.

Abstract: There is a metaphorical incoming tide of information technology (IT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Some of the efforts which had been made to develop the ability of teachers to develop assessment tools were looking at assessment and teaching-learning activities in an integrated manner. The teacher can carry out various assessment strategies within the teaching program to provide various types of information about student learning outcomes (Lee, Baker, & Haywood, 2018). The teachers need to consider various special needs of students.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the efforts which had been made to develop the ability of teachers to develop assessment tools were looking at assessment and teaching-learning activities in an integrated manner. The teacher can carry out various assessment strategies within the teaching program to provide various types of information about student learning outcomes (Lee, Baker, & Haywood, 2018). The teachers need to consider various special needs of students.…”
Section: Resultsmentioning
confidence: 99%
“…Outside of formal education environments, educational video resources supporting practitioners engaging in music production are widespread (Pensado 2013). These instructional videos can support learning, but it has been suggested they often target a broader audience, limiting their relevance to higher education coursework (Lee et al 2018). By producing video resources that are specific to the requirements of the cohort, a higher education (HE) institution offers students "active, contextual learning experiences" (Voss 2022: 24).…”
Section: Rationalementioning
confidence: 99%
“…Video use in music education has been led culturally through online communities where amateurs to professionals have been documenting different practices and techniques (Lee et al 2018). In an analysis by Lee and colleagues (2018), they found that although there was variable quality and accuracy in a few of the videos (teaching guitar technique) there was also an opportunity for educators to contribute to this immense body of content in terms of skillsets such as collaboration, professionalism, and support.…”
Section: Video Resources As Flipped Learningmentioning
confidence: 99%
“…Web-based distance guitar lesson examples started to increase thanks to the developments in technology and the internet. Today, guitar lessons websites offer a wide range of opportunities through performance and educational videos, live Q&A sessions, blogs, and forums covering guitar topics for guitar students (Lee et al, 2018). Examples to guitar lessons websites such as onlineguitaracademy (2021), justinguitar (2020), classicalguitarcorner (2021), and thisisclassicalguitar (2020), are global platforms for courses can be taken in different guitar types and music genres.…”
Section: Introductionmentioning
confidence: 99%